2013
DOI: 10.1016/j.cub.2013.04.046
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor Rb Critically Regulates Starvation-Induced Stress Response in C. elegans

Abstract: Summary How animals coordinate gene expression in response to starvation is an outstanding problem closely linked to aging, obesity, and cancer [1–5]. Newly hatched Caenorhabditis elegans respond to food deprivation by halting development and promoting long-term survival (L1 diapause), thereby providing an excellent model to study starvation response [2, 6, 7]. Through a genetic search, we have discovered that the tumor suppressor Rb critically promotes survival during L1 diapause and likely does so by regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…To understand the role of ceramide in regulating animal starvation survival, we screened all available, viable, C. elegans mutants in the ceramide metabolism pathways for altered L1 starvation survival rates (Cui et al 2013) ( Figure 1A and Table S1), and found many such mutants were significantly short-lived during L1 starvation ( Figure 1, A-C, Figure S1, A-C, and Table S1). Specifically, animals with mutations in the de novo ceramide biosynthesis pathway were sensitive to starvation-induced stress ( Figure 1, B-C and Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand the role of ceramide in regulating animal starvation survival, we screened all available, viable, C. elegans mutants in the ceramide metabolism pathways for altered L1 starvation survival rates (Cui et al 2013) ( Figure 1A and Table S1), and found many such mutants were significantly short-lived during L1 starvation ( Figure 1, A-C, Figure S1, A-C, and Table S1). Specifically, animals with mutations in the de novo ceramide biosynthesis pathway were sensitive to starvation-induced stress ( Figure 1, B-C and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The L1 starvation assay was done following the protocol described previously (Lee and Ashrafi 2008;Cui et al 2013;Zhang et al 2011b). Survival curves were drawn based on three or more independent experiments.…”
Section: L1 Starvation Survival Assay and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…How this information is transduced to affect gene expression in response to a given stimulus is currently speculative at best. During starvation in C. elegans L1 larvae, a specific geneexpression program is initiated (46) and during this period RNA polymerase II is observed in different configurations: in the "docked" state RNA polymerase II is on proximal promoters waiting for cues to initiate, whereas in the "paused" configuration the complex remains in a postinitiated state, presumably on hold until a physiological or developmental contingency is satisfied (47,48). This developmental pausing is not exceptional and in many organisms RNA polymerase II is maintained in a postinitiated state where subsequent elongation is regulated by factors that associate with the phosphorylated carboxyl-terminal domain of the RNA polymerase II large subunit (49).…”
Section: N="normal"mentioning
confidence: 99%